On the effects of increased time granularity in electricity spot markets - Santos, Eduard Renzo D.; Abrenica, Ma. Joy V. (Quezon City School of Economics, University of the Philippines Diliman, 2025)
This thesis investigates how shorter dispatch intervals affect electricity spot markets, particularly in the Philippine Wholesale Electricity Spot Market (WESM). Specifically, we look at how changing from hourly intervals to shorter five-minute intervals impacts market prices, the use of renewable energy, and market power. Since electricity cannot be stored easily, accurately matching supply with demand in real time is crucial. Shorter intervals improve forecasting, reduce forecasting errors, and thus enhance market efficiency by helping to balance supply and demand more precisely. Additionally, the thesis develops a theoretical basis for understanding how shorter dispatch intervals might enhance the integration of renewable energy sources, such as wind and solar. Given the inherently variable output of these resources, shorter intervals could encourage greater adoption and, thus, increased market competition. To shed more light on this, we also present initial findings that illustrate the dynamics of market competition. Applying a generalized autoregressive conditional heteroskedasticity interrupted time series (GARCH-ITS) approach to data from the Philippines, the analysis reveals that shorter dispatch intervals are associated with lower spot prices. These insights provide valuable guidance for policymakers and point to promising directions for future investigation.
Thesis (MA in Economics) - - University of the Philippines Diliman
Keywords: Electric utilities; Electric industries; Electrification -- Economic aspects